A new species of Galendromus (Acari: Phytoseiidae) : A case of intraspecific variation and redefinition of carinulatus species group - Demite, Peterson R. [UNESP]; Lofego, Antonio C. [UNESP]; Feres, Reinaldo J.F. [UNESP] (Oxford University Press (OUP), 2008)
A new species, Galendromus (Mugidromus) sulamericanus, is described from north-western São Paulo state, Brazil, and it is included in the carinulatus species group Chant and Yoshida-Shaul, which is herein redefined to accommodate this new species. A variation in the insertion of ZV2 seta in the ventral shield was observed in individuals from the same population. A key is provided for all known species of the subgenus Mugidromus Tuttle and Muma. © 2008 Entomological Society of America.
Keywords: Brazil; Carinulatus species group; Galendromus (Mugidromus); Predatory mites; South America